2013
DOI: 10.1007/s00216-013-7238-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of coumarin in cinnamon and woodruff beverages using DIP-APCI-MS and LC-MS

Abstract: The use of the direct inlet probe-atmospheric-pressure chemical ionization (DIP-APCI) ion source developed in our laboratory coupled to a high resolution Q-TOF MS for the quantitative analysis of coumarin in different cinnamon samples was demonstrated in this study. Extraction of coumarin from various cinnamon samples was followed by DIP-APCI-mass spectrometry (MS) and liquid chromatography (LC)-MS analysis. For quantification, an external calibration with and without the use of stable isotope-labeled coumarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…They are present at high levels in cinnamon and many fruits and vegetables (Krieger et al, 2013;Ribeiro da Silva et al, 2014). Different derivatives of these compounds possess a wide range of biological activities (Venugopala et al, 2013) such as antioxidant (Morabito et al, 2010;Natella et al, 2010;Pedersen et al, 2007), anti-inflammatory (Togna et al, 2014), antimicrobial (Gupta et al, 2012), and in vitro (Macakova et al, 2012) and in vivo platelet anti-aggregation effects .…”
Section: Introductionmentioning
confidence: 99%
“…They are present at high levels in cinnamon and many fruits and vegetables (Krieger et al, 2013;Ribeiro da Silva et al, 2014). Different derivatives of these compounds possess a wide range of biological activities (Venugopala et al, 2013) such as antioxidant (Morabito et al, 2010;Natella et al, 2010;Pedersen et al, 2007), anti-inflammatory (Togna et al, 2014), antimicrobial (Gupta et al, 2012), and in vitro (Macakova et al, 2012) and in vivo platelet anti-aggregation effects .…”
Section: Introductionmentioning
confidence: 99%
“…Plant researchers consider coumarins as a potential fluorescent and flavoring component (Poulton et al, 1980; Oba et al, 1981; Mock et al, 1999; Katerinopoulos, 2004; Bourgaud et al, 2006; Stanfill et al, 2007; Maggi et al, 2011; Krieger et al, 2013). Tracer experiments using cinnamate ( 10 ) or its derivatives have effectively shown that simple coumarin formation in plants proceeds via hydroxylation of the ortho -position ( ortho -hydroxylation) of respective cinnamates, the adjacent position in the benzene ring to the side chain (Brown et al, 1960; Brown, 1962; Fritig et al, 1970; Bayoumi et al, 2008a), followed by formation of a lactone ring.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, limits of detection (LOD), limits of quantification (LOQ) and coefficient of determination (R 2 ) were calculated and listed in Table 1. For comparison the values determined by Krieger et al [13] for the DIP-APCI are added and show that comparable values for LOD and LOQ are obtained with DIP-APPI.…”
Section: Analytical Limitsmentioning
confidence: 94%
“…It has been successfully applied to various samples such as Chinese drugs [11] and plasticizers [12]. Also quantification, which is still challenging with other types of ambient ion sources, is possible with this ion source as shown for coumarin in different cinnamon samples [13]. Additionally, extractive electrospray ionization (EESI) has been added to this ion source [14], which enables the detection of polar compounds without changing the ion source.…”
Section: Introductionmentioning
confidence: 99%